2022
DOI: 10.1039/d2nr03355k
|View full text |Cite
|
Sign up to set email alerts
|

Capture and electrochemical conversion of CO2 in molten alkali metal borate–carbonate blends

Abstract: A family of blended compositions of molten mixed lithium and sodium borate (Li1.5Na1.5BO3) and eutectic lithium-potassium carbonate (Li1.24K0.76CO3) salts has been introduced as reversible carbon dioxide absorbents and as media...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
0
12
1
Order By: Relevance
“…As shown in the Raman spectrum (Figure f), the noticeable G band and 2D band located at 1580 and 2700 cm –1 , respectively, further reveal that the carbon nanocoils deliver graphitic features. Similar one-dimensional nanostructured carbon nanofibers/nanotubes can also be found in borate-containing and Li 2 O-containing lithium carbonates. Considering that the oxygen content of carbonaceous materials plays an important role in their nanostructures and crystallinity, we speculate that the borates could help modulate the carbon growth environment’s oxo-acidity by regulating adjacent oxygen content and facilitating an ordered arrangement of carbon atoms in the basal planes, which needs systematic investigation in the future. It should be pointed out that the contrast between onset potential and theoretical potential for borate-involved CO 2 RR was only tens mV, implying that the overpotential to initiate CO 2 RR should be low.…”
Section: Cathodic Thermodynamics and Electrochemical Characterizationmentioning
confidence: 73%
“…As shown in the Raman spectrum (Figure f), the noticeable G band and 2D band located at 1580 and 2700 cm –1 , respectively, further reveal that the carbon nanocoils deliver graphitic features. Similar one-dimensional nanostructured carbon nanofibers/nanotubes can also be found in borate-containing and Li 2 O-containing lithium carbonates. Considering that the oxygen content of carbonaceous materials plays an important role in their nanostructures and crystallinity, we speculate that the borates could help modulate the carbon growth environment’s oxo-acidity by regulating adjacent oxygen content and facilitating an ordered arrangement of carbon atoms in the basal planes, which needs systematic investigation in the future. It should be pointed out that the contrast between onset potential and theoretical potential for borate-involved CO 2 RR was only tens mV, implying that the overpotential to initiate CO 2 RR should be low.…”
Section: Cathodic Thermodynamics and Electrochemical Characterizationmentioning
confidence: 73%
“…It can be noticed from Figure that all the samples, apart from NB2 (has a small peak), have significant peaks between 50 and 100 °C, which is related to the pre-adsorbed moisture . Another weight loss shown above 200 and 400 °C could be assigned to the release of crystalline water over multiple steps . NB1, NB3, and NB4 adsorbent materials presented another weight loss accompanied with an endothermic peak above 600 °C, which is related to the melting point of NB3 (664 °C) and NB4 (614 °C), which agrees with the sodium boron phase diagram (S-1) that presents the melting point above 600 °C.…”
Section: Resultsmentioning
confidence: 93%
“…However, it has been recently demonstrated that molten salt can function as an ideal electrolyte to capture, activate and convert CO 2 into advanced carbon and hydrocarbon [4–8] . This is due to a thermodynamically spontaneous reaction between CO 2 and O 2− in molten salts (Figure S1, Supporting Information), which thereby increases the solubility of CO 2 in molten salts to several moles per liter [9–12] . Molten salts also have larger electrochemical windows than that of aqueous solutions, making them less vulnerable to electrolyte decomposition.…”
Section: Figurementioning
confidence: 99%
“…[4][5][6][7][8] This is due to a thermodynamically spontaneous reaction between CO 2 and O 2À in molten salts (Figure S1, Supporting Information), which thereby increases the solubility of CO 2 in molten salts to several moles per liter. [9][10][11][12] Molten salts also have larger electrochemical…”
mentioning
confidence: 99%